2020
DOI: 10.1038/s41419-020-02984-y
|View full text |Cite
|
Sign up to set email alerts
|

CPEB3-mediated MTDH mRNA translational suppression restrains hepatocellular carcinoma progression

Abstract: Cytoplasmic polyadenylation element-binding protein 3 (CPEB3) is a sequence-specific RNA-binding protein. We had reported that CPEB3 is involved in hepatocellular carcinoma (HCC) progression. However, the underlying mechanisms of CPEB3 in HCC remain unclear. In this study, we firstly performed RNA immunoprecipitation to uncover the transcriptome-wide CPEB3-bound mRNAs (CPEB3 binder) in HCC. Bioinformatic analysis indicates that CPEB3 binders are closely related to cancer progression, especially HCC metastasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…The detailed method for carryout quantitative real-time PCR (qRT-PCR) is previously described ( Zhang et al, 2020 ). Briefly, cells were lyzed using TRIzol reagent (Life Technologies, Carlsbad, CA, United States), and the RNA was isolated and reverse transcribed into cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed method for carryout quantitative real-time PCR (qRT-PCR) is previously described ( Zhang et al, 2020 ). Briefly, cells were lyzed using TRIzol reagent (Life Technologies, Carlsbad, CA, United States), and the RNA was isolated and reverse transcribed into cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…It was documented that cytoplasmic polyadenylation element-binding protein 1 (CPEB1) binds to AEG-1 mRNA and increases its translation in glioblastoma cells [ 163 ]. On the other hand, in HCC cells, CPEB3, which functions as a tumor suppressor, binds to the 3′-untranslated region of AEG-1 mRNA and inhibits its translation [ 164 ]. Thus, AEG-1 overexpression in cancer occurs at all levels of gene regulation.…”
Section: Astrocyte-elevated Gene-1 (Aeg-1): An Oncogene Implicated In Diverse Cancersmentioning
confidence: 99%
“…Present literature has confirmed that CPEB3 is vital in the progression of HCC. 29 For example, the study of Zhang et al 18 showed that CPEB3 can restrain EMT of HCC cells, and mice with CPEB3 knockout were more prone to develop liver cancer and lung metastasis. MiR-224 performs a tumor-promoting effect in HCC malignancies by targeting CPEB3.…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al 17 found that CPEB3 is down-regulated in cervical cancer. The study of Zhang et al 18 manifested that CPEB3 inhibits EMT of HCC cells, and mice with CPEB3 knockout are more prone to develop HCC and lung metastasis. These studies suggest that CPEB3 is vital in modulating the growth and development of various tumors, including HCC.…”
Section: Introductionmentioning
confidence: 99%